Isotopic (δ2H) Analysis of Stored Lipids in Migratory and Overwintering Monarch Butterflies (Danaus plexippus): Evidence for Southern Critical Late-Stage Nectaring Sites? - Hobson, Keith A.; García-Rubio, Oscar R.; Carrera-Treviño, Rogelio; Anparasan, Libesha; Kardynal, Kevin J.; McNeil, Jeremy N.; García-Serrano, Eligio; Mora Alvarez, Blanca X. (Frontiers in Ecology and Evolution, 2020)
Monarch butterflies (Danaus plexippus) fuel their migration and overwinter energy needs through accumulated fat stores derived from plant nectars. Determining origins of these fuels is crucial to effective conservation programs. We used stable-hydrogen (δ2H) and carbon (δ13C) isotope measurements in stored lipids of monarchs raised under laboratory conditions as a proof of principle for the isotopic spatial sourcing of stored lipids. We then applied this approach to wild specimens collected from 2015 to 2018 to infer spatial information on nectaring by fall migrants through northeast Mexico and at the Mexican overwinter sites. Migrating monarchs derived from wide geographic natal origins but lipid δ2H values from migratory cohorts were not related to natal origin. Instead, migrants exploited isotopically similar nectar sources. Distributions of lipid δ2H values in overwintering monarchs were broader and more negative by 40‰ suggesting more transport of lipids from higher latitudes or additional nectaring while migrating at higher elevations though northeastern to central Mexico. Our work establishes a new isotopic technique for tracking origins of stored lipids in monarchs and other migratory animals and emphasizes the importance of nectar availability in the southern portion of the range, and especially the nectar corridor through central Mexico.